RETRACTED: Investigation on the Mechanical Properties of Fiber Reinforced Recycled Concrete - Hasan Jalilifar; Fatholla Sajedi; Sadegh Kazemi (Civil Engineering Journal, 2016)
This article has been retracted: please see Civil Engineering Journal policies:(https://www.civilejournal.org/index.php/cej/about/editorialPolicies).This article has been retracted at the request of the Editor-in-Chief. Violation of rules: submitting articles without approval of all coauthors.